1984
DOI: 10.1073/pnas.81.15.4922
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene E4-induced airway hyperresponsiveness of guinea pig tracheal smooth muscle to histamine and evidence for three separate sulfidopeptide leukotriene receptors.

Abstract: Bronchial hyperresponsiveness to contractile agonists and nonspecific irritants is a characteristic feature of bronchial asthma. The mechanisms causing this hyperirritability are unknown. The existence of separate receptors for leukotrienes C4 and D4 (LTCC4 and LTD4) has been, demonstrated previously by physiologic and radioligand binding studies. The rank order of potency of the sulfidopeptide leukotrienes for contracting tracheal spirals [leukotrwiene E4 (LTE4) > LID4 = LTC4J is different from that for contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(62 citation statements)
references
References 27 publications
(21 reference statements)
1
59
0
Order By: Relevance
“…In contrast, pretreatment with LTE 4 , but not LTC 4 or LTD 4 , enhanced the response of guinea pig trachea (9) or human bronchial smooth muscle to histamine (10). Furthermore, in limited studies, LTE 4 was comparable with LTC 4 or LTD 4 in eliciting a vascular leak in skin in guinea pigs (11) or humans (12), and inhalation of LTE 4 , but not LTD 4 , by patients with asthma elicited an accumulation of eosinophils and basophils into the bronchial mucosa (13,14).…”
mentioning
confidence: 71%
“…In contrast, pretreatment with LTE 4 , but not LTC 4 or LTD 4 , enhanced the response of guinea pig trachea (9) or human bronchial smooth muscle to histamine (10). Furthermore, in limited studies, LTE 4 was comparable with LTC 4 or LTD 4 in eliciting a vascular leak in skin in guinea pigs (11) or humans (12), and inhalation of LTE 4 , but not LTD 4 , by patients with asthma elicited an accumulation of eosinophils and basophils into the bronchial mucosa (13,14).…”
mentioning
confidence: 71%
“…It may be concluded that, under physiological conditions, neither LTC4 nor LTD4 induces increased responsiveness to histamine on airways smooth muscle. However, the sensitivity oftracheal smooth muscle to histamine determined by Lee et al, (1984) was considerably less (approx. 0.7 log units) that that determined in the present study and by other workers (cf.…”
Section: Analyses Of Datamentioning
confidence: 97%
“…This occurred (i) under conditions of lowered Ca2" concentration (0.1 mM), but not where Ca2+ (2.5 mM) was used (Creese & (Lee et al, 1984). It may be concluded that, under physiological conditions, neither LTC4 nor LTD4 induces increased responsiveness to histamine on airways smooth muscle.…”
Section: Analyses Of Datamentioning
confidence: 99%
See 2 more Smart Citations